Sistem Pendukung Keputusan Kawasan Kumuh Kota Semarang Menggunakan Metode Copras Dengan Data Vitalitas Non Ekonomi Sebagai Data Kriteria - Saifur Rohman Cholil; Yudi Prayoga; Yudi Cahyono; Susanto Susanto (Department of Science and Technology Ibrahimy University, 2023)
Semarang City is the capital of Central Java Province which has a location in the middle of the province. Its strategic location is on the route across the North Coast of Java Island which connects major cities on Java Island. The high population in the city center requires the fulfillment of the need for livable housing, especially to accommodate urbanists whose jobs are concentrated in the trade and service sectors in the commercial area in the city center. The availability of complete facilities and infrastructure in the city center is also an attraction for people to live in the area. With the income level and economy of the community less so high, without realizing it, the need for livable settlements is difficult to accommodate. This study aims to build a decision support system (DSS) for the determination of Slum Areas in Semarang City using the COPRAS method. The COPRAS method has a good degree of selectivity because it can determine the purpose of conflicting criteria. System implementation is done using PHP language and MySQL database. The SPK that was built was able to produce recommendations by providing the ranking of slum areas to users.